Periprosthetic infection: diagnostic and treatment. Part 1 (literature review) - Filipenko, Volodymyr; Marushchak Оleksey; Bondarenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">Hip and knee joints replacement became widespread in the world and Ukraine due to their high efficiency and improvement of life quality. However, similar to any other surgical intervention, it is not without complications. Periprosthetic infection is among the most difficult complications because it could easily negate all the efforts of the surgeon and patient to achieve a positive result. Very little attention was paid to this very serious disease in Ukrainian medical journals. The authors have presented information from scientific literature concerning the possibilities of various modern diagnostic techniques used to determine periprosthetic infections. The most widely used classifications are described. The modern diagnostic criteria that based on International Consensus Conference on periprosthetic infection (2013) and used as a basis for diagnosis establishing are provided. Such diagnostic tests as serologic (C-reactive protein, erythrocyte sedimentation rate, interleukins, procalcitonin, tumor necrosis factor, and combinations there of) microbiological, synovial, histological are listed from the standpoint of their sensitivity and specificity in the preoperative and intraoperative phases, their thresholds are presented. The authors systematized information to determine the main pointsof dignostics and treatment of this complication. The necessity in early and most complete diagnostics of infection with accurate determining of the pathogen is emphasized since the choice of optimal treatment (surgical and antibacterial) is based on these results. Only with the right method of treatment chosen, based on accurate and timely diagnostics, doctor and patient can expect success in the fight against infection.